Massive Methane Loss During Seasonal Hypoxia/Anoxia in the Nearshore Waters of Southeastern Arabian Sea - Sudheesh, V.; Gupta, G. V. M.; Naqvi, S. W. A. (Frontiers in Marine Science, 2020)
Repeat observations over the Kochi and Mangalore shelves of the southeastern Arabian Sea (SEAS) during April to December 2012 revealed substantial accumulation of methane (CH4) in the nearshore waters (48.6±34.4 nM) compared to the outer shelf (2.9±0.7 nM). Sediment methanogenesis and estuarine discharge appear to be the major sources of CH4 in the nearshore regions during non-upwelling period. But under oxygen deficient conditions that prevail during the upwelling period, extremely low concentrations of CH4 in the nearshore anoxic region of Mangalore (14±2 nM) compared to similar region of hypoxic Kochi shelf (35.5±15.4 nM) have been observed. We propose that this is mainly due to its greater loss through anaerobic oxidation and in part by the reduced sedimentary inputs by weak bioturbation over Mangalore relative to Kochi. On an annual basis, SEAS is found to be a net source of CH4 to the atmosphere with its efflux ranging from 0.03 to 170 µmol m-2 d-1 (21.9±36.7 µmol m-2 d-1). Following a zonal extrapolation approach, the estimated CH4 efflux from the SEAS (7-14oN; 3.2 Gg y-1) accounts for up to ~16 % of the total CH4 emission from the Arabian Sea.